2018
DOI: 10.1002/jcla.22579
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of combined and noncombined dyslipidemia in an Iranian population

Abstract: Background Combination of dyslipidemic phenotypes, including elevated plasma levels of low‐density lipoprotein cholesterol (LDL‐C), elevated plasma triglycerides (TG), and decreased low‐density lipoprotein cholesterol (HDL‐C) concentrations, is important because of the association of individual phenotypes with increased risk of cardiovascular disease (CVD). We investigated the prevalence of combined dyslipidemias and their effects on CVD risk in an Iranian large population. Method A total of 9847 individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
13
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
7
13
5
Order By: Relevance
“…In our study, the overall prevalence of dyslipidemia (at least one abnormal lipid profile value) was 86.7%. This result is similar to that reported in an Iranian study (83.4%) study 39 . However, our figures are higher than those in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the overall prevalence of dyslipidemia (at least one abnormal lipid profile value) was 86.7%. This result is similar to that reported in an Iranian study (83.4%) study 39 . However, our figures are higher than those in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, one recent study conducted in KSA reported a 78% prevalence of dyslipidaemia, which is lower than our figures 28 Furthermore, other regional and international studies conducted in Egypt, Turkey, and the United States estimated the prevalence of dyslipidaemia, that is, 63.8%, 78.7%, and 65%, respectively 17 , 20 , 29 . On the contrary, our results are similar to that of an Iranian study that reported a prevalence rate of 83.4% for dyslipidaemia 30 …”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of hypercholesterolemia, hypertriglyceridemia, high levels of LDL-C, and low levels of HDL-C are reported to be 41.6, 46.0, 35.5, and 43.9%, respectively in both sexes in the Iranian population [7]. Darroudi et al have recently reported the prevalence of dyslipidemia among a subsample of Iranian adults to be 83 and 87% in the total population and CVD patients, respectively [8].…”
Section: Introductionmentioning
confidence: 99%